Återföring av växtnäringsämnen från avloppsvatten till åkermark : en bedömning av intresset för nya näringsrika produkter - Broström, Ulrica (SLU/Dept. of Soil Sciences, 2007)
Sewage sludge contains plant nutrients and has earlier been utilised as fertilizer to cropland. Unfortunately not only plant nutrients but also heavy metals, pathogens and organic contaminants tend to accumulate in sludge. The suitability to use sewage sludge in agriculture has therefore been subject to several discussions over the years. The Swedish food industry does no longer accept sludge as fertiliser for Swedish producers.